High temperature oxidation and interdiffusion behavior of recoated NiCoCrAlY coating on a nickel-based superalloy. (October 2020) - Wang, Jinlong; Ji, Hongyan; Chen, Minghui; Bao, Zebin; Zhu, Shenglong; Wang, Fuhui
Highlights: A NiCoCrAlY coating that has been oxidized at high temperature is removed by electrochemical stripping. The recoated coating exhibits lower oxidation rate, but is more likely to spall off during cyclic oxidation. Elements interdiffusion with the alloy substrate causes the difference in oxidation behavior. The consumption of Al in the recoated coating was larger than that in the ordinary one after diffusion into the alloy. Abstract: NiCoCrAlY coating that has been oxidized at high temperature is successfully removed by electrochemical stripping from a nickel-based superalloy, which is followed by recoating a fresh one. Then oxidation behavior of the recoated NiCoCrAlY coating is investigated in comparison with the ordinary one. Results indicate that the recoated coating exhibits a lower oxidation rate with a rate constant of 3.1×10 −14 g 2 cm -4 s -1 at 1000 °C. However, its oxide scale is more likely to spall off than that of the ordinary one in cyclic oxidation. Elements interdiffusion between the NiCoCrAlY coatings and the alloy substrate leads to the different oxidation behavior.